Exploring the Impact of Social Media on Political Participation: A Review of Empirical Studies - Sjoraida, Diah Fatma; Guna, Bucky Wibawa Karya; Nungraha, Aat Ruchiat; Amri, Miftachul; Santosa, Tomi Apra; Suar, Abi (Universitas Pahlawan Tuanku Tambusai, 2024)
Politicians around the world are increasingly using social media platforms as a means to engage with the public and conduct election campaigns. However, the true impact of social media campaigns on political outcomes remains untested and empirical evidence is scant. This research aims to review the existing literature on this issue to explore the impact of social media on political participation. The widespread use of social media by the public has attracted the attention of politicians as a platform for election campaigns. This type of research is a literature review by analyzing previous research qualitatively. The results show that social media has a significant impact on political participation. Social media platforms provide powerful new tools for individuals to engage in the political process and make their voices heard. However, it is important to be aware of the potential challenges of using social media for political participation and to use it responsibly and ethically. Social media has a significant role in expanding access to political information, mobilizing public participation, and reaching marginalized voters. Social media provides an inclusive platform for individuals to participate in political discussions, organize political movements, and strengthen democracy by ensuring the voices of all citizens are heard. However, challenges such as the digital divide and imbalances in social media use also need to be addressed so that the full potential of social media in democracy can be realized. Therefore, joint efforts from governments, NGOs, social media platform providers and the general public are needed to ensure that social media is used responsibly and inclusively in supporting democratic political processes.